PATRIARCHAL CULTURE AND EDUCATIONAL BARRIERS: A PARSONIAN STRUCTURAL FUNCTIONAL ANALYSIS OF GENDER INEQUALITY IN HIGHER EDUCATION IN JAMPANG VILLAGE - Azahra, Fatimatu; Komariah, Siti; Wulandari, Puspita (Kafa`ah: Journal of Gender Studies, 2024)
This study examines gender inequality in higher education in Jampang Village, Gunung Sindur District, Bogor Regency. The issue of gender inequality is still relevant because it is related to the principles of morality and justice, and is important in achieving sustainable development goals (SDGs). The study used a qualitative approach with a case study method, involving interviews with five women in Jampang Village who did not continue their higher education. Data was also obtained through observation and literature study. The results of the study show that gender inequality in education is caused by a patriarchal culture that places men in a more dominant role and limits women's access to education. Women in Jampang Village are often forced to marry after graduating from high school to ease the economic burden on their families, with the support of parents who believe that women's roles are limited to household affairs. The inability to continue their education limits their career opportunities and makes it difficult for them to find decent work. Factors that hinder women from continuing their higher education include family pressure, financial constraints, and household responsibilities. Analysis using Talcott Parsons' structural functional theory highlights that gender inequality is the result of social structures that support discrimination against women. Therefore, to overcome gender inequality, it is necessary to change the mindset of society and have government policy support that ensures equal access to education for women and men. Recommendations include developing gender-sensitive curricula to eliminate gender discrimination and raising public awareness of the importance of higher education for women.